An analysis of the students' perception of the student services in Ateneo de Davao high school department during school year 1977-78 - Potestas, Alfredo B. (Animo Repository, 1978)
The study sought to determine which areas of the student services are fully and poorly rendered by the school to the students. Specifically, the study aims to answer the following questions : 1) Are the students satisfied with the existing student services? 2) What is the hierarchy of preferences of students with regards to the student services per year level? The descriptive survey method of investigation was used to gather data from the three hundred students of the second, third and fourth year levels of Ateneo de Davao. They were selected through random sampling. For the statistical treatment of data, the analysis of variance and t-test were used.